Pemanfaatan Aplikasi Parental Control Sebagai Media untuk Mewujudkan Internet Sehat dan Aman - Aryanti, Utami (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
The use of the internet must be in accordance with applicable ethics and norms. The internet must be used for positive activities and not harm yourself or others. Healthy internet is the concept of using the internet to protect yourself and others from possible dangers or risks in the online world. Referring to the press release of the Indonesian Child Protection Commission (KPAI), the number of complaints related to special child protection cases in 2021 was 2,982 cases. Of these, 345 cases were related to cybercrime (internet crime). As many as 64% of internet users in Indonesia are teenagers aged 15 to 19 years, so the role of parents is very important in supervising their children's behavior when using the internet. Parental control is software (software) or equipment that allows parents to control, limit and regulate the use of the internet for children. This activity aims to educate parents regarding the use of parental control applications to supervise children and adolescents in internet use. The method used in this research is Community Based Research (CBR). Helps make it easier for parents to supervise children's internet use to avoid negative content.